Constructing the Olympic Dream: A Future Perfect Strategy of Project Management - Pitsis, Tyrone S.; Clegg, Stewart R.; Marosszeky, Marton; Rura-Polley, Thekla (Organization Science, 2003)
In this paper we investigate a uniquely complex organizational context—that of the fast-tracked large-scale project management of a significant piece of Sydney 2000 Olympic infrastructure, which we researched in terms of its management through the “future perfect.” In a grounded analysis we resolved to track how the future perfect developed in the life of one large, complex project whose uniqueness meant that it was unable to be strategically planned in advance. We tracked the use of what we term “future perfect strategy” through analysis of data collected both in leadership meetings of the directing agency, “PALT”—Project Alliance Leadership Team—as well as in individual interviews that we conducted in and around the project, and through analysis of media coverage. Overall, the project was a success, but some problems arose along the way to completion. Largely, these were focused on issues of social rather than technical construction—something even the most strategic of plans cannot account for. As well as identifying some of the specific mechanisms for encouraging future perfect strategy that were used in the project, including encouraging “strange conversations,” “playing end games,” “workshopping,” and “projecting feelings, concerns and issues,” we also suggest some ways that the social construction issues might be handled in the future.